Breaking Dormancy Barriers: Harnessing Fermented Plant Juice (FPJ) for Enhanced Germination and Early Seedling Growth in Lettuce (Lactuca sativa L.) - Fronda, Angelica Joy; Valdez, Manolo (Journal of Interdisciplinary Perspectives, 2025)
Lettuce (Lactuca sativa L.) is a widely cultivated leafy vegetable, but seed dormancy and slow, uneven germination often limit crop uniformity and yield. Finding natural, sustainable methods to improve seed germination and early seedling growth is essential for enhancing lettuce production. The study investigated the effect of Fermented Plant Juice (FPJ), a bio-stimulant made from natural plant extracts, on lettuce seed germination and seedling development. Four treatments were tested: a control with no treatment, and FPJ solutions at 2%, 5%, and 10% concentrations. Seeds were monitored for 8 days to assess germination rates and then for an additional 12 days to evaluate seedling emergence and growth vigor. The highest germination rate of 98.67% was observed with the 10% FPJ treatment by Day 7, with seedling emergence reaching 100% by Day 11, starting from 17.67% on Day 3. The 5% FPJ treatment also significantly improved germination and emergence, approaching full seedling development by Day 12. The 2% FPJ treatment showed moderate improvement compared to the control, which had the slowest germination and poorest seedling growth. These findings demonstrate that FPJ can effectively break seed dormancy, accelerate germination, and promote uniform and vigorous seedling growth. Using FPJ as a natural seed treatment provides a cost-effective and eco-friendly alternative to chemical stimulants, supporting sustainable agricultural practices. The application of FPJ can contribute to higher crop yields and better-quality lettuce seedlings, making it a promising tool for farmers and researchers aiming to improve lettuce production naturally.